(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
The article about the improving personal and social hygienic skills in children plays an important role in protecting their health and contributes to the correct behavior in everyday life, in public places. Finally, not only their health, but also the health of other children and adults, depends on the knowledge and fulfillment of the necessary hygienic rules and behavioral norms of children. In the process of daily work with children, it is necessary to strive so that the implementation of the rules of personal hygiene into life becomes natural and their hygiene skills are always improved with age.